Research on optical properties of cardiovascular tissues based on OCT data - Na Qin; Yana Liu; Lin Huang; Yi Xin; Xiao Zhang; Xiaoming Hu; Qin Li (Journal of Innovative Optical Health Sciences, 2021)
As a high-resolution optical imaging technology, Optical Coherence Tomography (OCT) has been widely used in the diagnosis and treatment of cardiovascular diseases. It has played an important role in the detection and identification of atherosclerotic plaques and has significant advantages. In this paper, we realized to extract the optical characteristic parameters of the target sample based on the OCT data by establishing optical transmission models conforming to the OCT principle. The optical phantoms and coronary artery of domestic pig were used as research samples to study the difference between the optical properties of the cardiovascular tissues. It can provide a basic method for further study of optical characteristic parameters of atherosclerotic plaques, and also lay a foundation for realizing the quantitative evaluation of atherosclerotic plaques with multiple optical characteristic parameters in the future.